A Review Of Legal Problems In Malaysian Strict Product Liability Law – Maqasid Syariah As A Way Forward - Mohd Shukri, Muhammad Hafiz; Markom, Ruzian; Ismail, Rahmah (Universiti Sultan Zainal Abidin, 2020)
Consumers who suffer from injury or property damage due to the existence of a defect in a given product is entitled to bring a legal action in court based on product liability law provisions in Malaysia. This study aims to analyse the legal problems of strict civil liability in product liability law in Malaysia based on the Consumer Protection Act 1999 (Act 599) (hereinafter “CPA 1999”). By applying a doctrinal approach based on qualitative methodology of legal research, this study involved a thorough analysis of the CPA 1999 as well as previous court cases. The findings of this study were analysed using content analysis and critical analysis methods in order to record the similarities and differences which exist, as well as to draw conclusions on the meaning and application of the said law. The findings prove that there are several weaknesses in the existing strict civil product liability provisions in Malaysia, which are still unresolved in terms of the meaning of product defect and proof of causation. This paper recommends that any improvements on the legal provisions for strict civil liability under product liability law in Malaysia to be evaluated from a different perspective based on Islamic principles of product liability and the theory of Maqasid Syariah, which has rarely been analysed.